2013
DOI: 10.5550/sgia.130901.en.007b
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rebounded Balls in a Team Handball Match

Abstract: SUMMARYWe have analysed fifteen matches played by the male Croatian national handball team at the World Championship in Tunisia in 2005 and those played at the European Championship in Austria in 2010. The research has been conducted with the purpose of establishing the frequency of shooting from certain zones, i.e. from the attacking positions, the frequency of rebounded balls off the goal keeper or off the goal frame, as well as establishing where or who to the performed shots rebound. The field for the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As is the case with offensive actions resulting from dead balls, this result could be because the opponent has an opportunity to organize their defense before the sequence begins. The quality of transferring from the position defense into transition attack depends on the speed of returning the ball back in the game by the goalkeeper (Burger et al, 2013). However, these data should be analyzed with some caution due to the small number of occurrences recorded.…”
Section: Losing >5mentioning
confidence: 99%
“…As is the case with offensive actions resulting from dead balls, this result could be because the opponent has an opportunity to organize their defense before the sequence begins. The quality of transferring from the position defense into transition attack depends on the speed of returning the ball back in the game by the goalkeeper (Burger et al, 2013). However, these data should be analyzed with some caution due to the small number of occurrences recorded.…”
Section: Losing >5mentioning
confidence: 99%
“…In order for the athletes to reach their potential, sports staff aims to improve and develop all performance components. It has been demonstrated that athletic performance and the time zones of the day in which this performance is realized, in other words, circadian rhythm are related (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In studies conducted in different groups, it was found that the power changes between 3% and 21.2% in different time zones of the day (6,9,14).…”
Section: Introductionmentioning
confidence: 99%
“…The studies indicate that, at the professional national levels, the full-step cycle, with three previous steps, is the most used [16][17][18]. However, in the modern international game of handball, the mobility of the defense players is continuously increasing, leading to more open defensive systems, and positioning the attacking players further away from the goal area than in traditional handball defenses.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the modern international game of handball, the mobility of the defense players is continuously increasing, leading to more open defensive systems, and positioning the attacking players further away from the goal area than in traditional handball defenses. Consequently, they do not give the thrower too much time to prepare the movement [16,19,20]. Therefore, some authors highlight the importance of mastering the technical-tactical resources of handball to succeed in competition [6,[21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%